FAKTOR KEBERLANJUTAN PENGGUNAAN IUD BERDASARKAN TEORI HEALTH BELIEF MODEL - Purwoning Husnul C; Esti Yunitasari; Erna Dwi W (Pediomaternal Nursing Journal, 2014)
Recently IUD is widely use for long-term contraception method but the usage tendency decrease the number of year. IUD discontinuations rise up. So far, factors related to IUD continuation had not been explained. Health belief model predicts the health behavior focused on belief and attitude. Thus may explain people action of IUD continuation. The aim of this research is to analyze factors related to the IUD continuation use based on health belief model. The research design was descriptive analysis with cross sectional approach. The population was 377 fertile couples IUD acceptors, and found 57 people that comply inclusive criterias that be done by purposive sampling. The dependent variable was IUD continuation, while perceived benefits, perceived barriers, self efficacy, and cues to action belong to independent variable. The instrument used was questionnaire. Spearman rho and chi squre statistical test was used in data analysis. The research results showed the correlation between perceived benefits and IUD continuation use (p=0,000; r =0,826), perceived barrier and IUD continuation use (p=0,000; r=0,708), self-efficacy and IUD continuation use (p=0,000; r=0,708), cues to action and IUD continuation use (p=0,011; r=0,336) in person category (p=0,005; r=0,365) in event category. In conclusion, the strongest factors that related to the IUD continuation use is perceived benefits. It has suggested to engage other factors on HBM such as aim of reproduction, sosioeconomic, husband’s occupation, threat also establish exact intervention to maintain behavior